2011
DOI: 10.1002/alr.20076
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of intraoperative computed tomography imaging for endoscopic sinonasal and skull‐base surgery

Abstract: Intraoperative CT scanning may hold important utility in selected endoscopic sinonasal and skull base procedures with additional interventions being performed in 18% of cases. The present study was unable to identify specific factors that would preoperatively predict the need for intraoperative imaging. Future clinical trials should include a multi-institutional design to better delineate these important variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In contrast, the mobile CT systems can be used in existing surgery rooms and can be even easily transported between several surgery rooms. Batra et al demonstrated usage of mobile intraoperative CT system (xCAT, Xoran Technologies, Ann Arbor, MI, USA) without automatically-registered neuronavigation at the conclusion of endoscopic sinonasal and skull-based surgeries and in 18% of cases they performed additional intervention [ 8 ]. However, the automatically-registered navigation using xCAT mobile CT system with submillimeter accuracy (0.34 mm average) has been successfully demonstrated recently on phantoms and could be point of future studies [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the mobile CT systems can be used in existing surgery rooms and can be even easily transported between several surgery rooms. Batra et al demonstrated usage of mobile intraoperative CT system (xCAT, Xoran Technologies, Ann Arbor, MI, USA) without automatically-registered neuronavigation at the conclusion of endoscopic sinonasal and skull-based surgeries and in 18% of cases they performed additional intervention [ 8 ]. However, the automatically-registered navigation using xCAT mobile CT system with submillimeter accuracy (0.34 mm average) has been successfully demonstrated recently on phantoms and could be point of future studies [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, use of intraoperative CT scanning resulted in additional intervention being performed in 18% of cases, demonstrating an important adjunctive role that may improve clinical outcomes. 14…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative surgical navigation is invaluable and intraoperative imaging can be beneficial in particular skull base pathologies. 84-88…”
Section: Endoscopic Endonasal Approachmentioning
confidence: 99%
“…Intraoperative surgical navigation is invaluable and intraoperative imaging can be beneficial in particular skull base pathologies. [84][85][86][87][88] The patient is placed in a semi-recumbent position to optimize venous outflow. The degree of head rotation and neck extension/flexion depends on the location and characteristics of the lesion.…”
Section: General Backgroundmentioning
confidence: 99%